Outcomes of percutaneous coronary intervention (PCI) among patients with connective tissue disease: Propensity match analysis. (1st April 2020) - Alliu, Samson; Ugwu, Justin; Babalola, Omotooke; Obiagwu, Chukwudi; Moskovits, Norbert; Ayzenberg, Sergey; Hollander, Gerald; Frankel, Robert; Shani, Jacob
Abstract: Background: Inflammation is the hallmark of coronary artery disease (CAD) and CTD. There are reports of increased prevalence of CAD among patients with CTD such as Rheumatoid Arthritis. However, there is a paucity of data regarding the outcomes of PCI among patients with CTD. Methods: Using the National Inpatient Database, patients that underwent PCI between 2007 and 2015 were identified using ICD-9-CM codes. Propensity match analysis with 1: 3 matching of patients with and without CTD was performed. Outcomes were acute kidney injury (AKI), access site complication (ASC), ventricular fibrillation (VF), cardiogenic shock (CS), Stroke, In-hospital mortality and hospital length of stay (LOS) compared between both groups. Result: We identified 17, 422 patients with CTD and matched with 52, 266 patients without CTD. Patients were predominantly female (63.1%) and white (77.2%), with a mean age of 63 ± 12.1 years. AKI (8.3% vs. 6.6%, p  < 0.001), ASC (3.2% vs. 2.7%, p  = 0.01) and hospital stay (4.2 ± 4.8 vs. 3.8 ± 5.2, p  < 0.001) were higher among patients with CTD. There was no statistically significant difference in rates of VF, CS, stroke, and In-hospital mortality among the two groups. However, in subgroup analysis, rates of VF were lower among patients with Systemic Lupus Erythematosus (SLE) (1.5% vs. 2.2%, p  = 0.006). Conclusions: Patients with CTD undergoing PCI have a higher rate of AKI, Access site complications, and prolonged hospital stay. Highlights: Rates of acute kidney injury (AKI) and access site complications were higher among patients with CTD that underwent PCI. No difference in the rates of stroke, ventricular fibrillation, cardiogenic shock and In-hospital mortality. Patient with CTD stayed longer in the hospital following PCI compared to patients without CTD.